Epidemiological patterns of chronic kidney disease attributed to type 2 diabetes from 1990-2019 - Ding, Xiaoxiao; Li, Xiang; Ye, Yun; Jiang, Jing; Lu, Mengsang; Shao, Lv (Frontiers in Endocrinology, 2024)
Background: This study investigates the burden of chronic kidney disease attributed to type 2 diabetes (CKD-T2D) across different geographical locations and time periods from 1990 to 2019. A total of 204 countries and regions are included in the analysis, with consideration given to their socio-demographic indexes (SDI). The aim is to examine both spatial and temporal variations in CKD-T2D burden. Methods: This research utilized data from the 2019 Global Burden of Diseases Study to evaluate the age-standardized incidence rates (ASIR), Disability-Adjusted Life Years (DALYs), and Estimated Annual Percentage Change (EAPC) associated with CKD-T2D. Results: Since 1990, there has been a noticeable increase of CKD age-standardized rates due to T2D, with an EAPCs of 0.65 (95% confidence interval [CI]: 0.63 to 0.66) for ASIR and an EAPC of 0.92 (95% CI: 0.8 to 1.05) for age-standardized DALYs rate. Among these regions, Andean Latin America showed a significant increase in CKD-T2D incidence [EAPC: 2.23 (95% CI: 2.11 to 2.34) and North America showed a significant increase in CKD-T2D DALYs [EAPC: 2.73 (95% CI: 2.39 to 3.07)]. The burden was higher in male and increased across all age groups, peaking at 60-79 years. Furthermore, there was a clear correlation between SDI and age-standardized rates, with regions categorized as middle SDI and High SDI experiencing a significant rise in burden. Conclusion: The global burden of CKD-T2D has significantly risen since 1990, especially among males aged 60-79 years and in regions with middle SDI. It is imperative to implement strategic interventions to effectively address this escalating health challenge.